The role of computed tomography and magnetic resonance imaging for preoperative pediatric cochlear implantation work-up in academic institutions. (4th March 2021) - Ambrosio, Art A.; Loundon, Natalie; Vinocur, Daniel; Kruk, Peter; Le Pointe, Hubert Ducou; Chalard, Francois; Zapala, Matthew; Carvalho, Daniela
Abstract : Objective: The goal of the study is to investigate the association of pertinent preoperative temporal bone computed tomography (CT) and brain magnetic resonance imaging (MRI) results and intraoperative surgical findings and complications of pediatric cochlear implantation reported in academic settings. Methods: This is a retrospective review of cochlear implant patients who received a pre-operative temporal bone CT and MRI of the brain between 2005 and 2012 at academic pediatric otolaryngology practices within children's hospitals in the United States and France. Scans were reviewed in a double-blind fashion and compared to intraoperative findings. Results: 91 children were analyzed (mean age 5.54 +/− 0.58 years). A small facial recess identified on CT was associated with difficult insertion of electrodes ( P = 0.0003). A prominent sigmoid sinus noted on CT was associated of difficult insertion of electrodes ( P = 0.01), iatrogenic tegmen dehiscence ( P = 0.005), as well as difficult round window access ( P = 0.025). No specific CT finding was found to be associated with external auditory canal injury, perilymphatic gusher, or iatrogenic facial nerve injury. MRI brain and internal auditory canal findings were not predictive of surgical outcomes. Conclusions: Preoperative CT and MRI remain an important planning tool for pediatric cochlear implantation, particularly in academic institutions. The findings of our study demonstrate that a detailed assessment of both preoperative CT and MRI are valuable for teaching and surgical planning.